A detailed analysis of the MAO TiO2 coating hardness using the Jönsson and Hogmark “law-of-mixtures” model - Cardoso, Giovana Collombaro [UNESP]; Kuroda, Pedro Akira Bazaglia [UNESP]; Grandini, Carlos Roberto [UNESP] (Elsevier, 2023)
This paper investigated the microhardness of a porous oxide coating produced on CP-Ti using the micro-arc oxidation technique (MAO) and conducted a detailed investigation of the coating's microhardness. The surface pores number, anatase/rutile phase ratio, and coating thickness influenced performed the Vickers indentations. Therefore, the Jönsson and Hogmark model was used to accurately calculate the average microhardness value, excluding the influence of the substrate hardness. The hardness value of the MAO coating on the CP-Ti substrate was (130 ± 30) HV.
Keywords: Micro-arc oxidation; Microhardness measurement; Titanium